2010
DOI: 10.1063/1.3308483
|View full text |Cite
|
Sign up to set email alerts
|

Correlation consistent basis sets for molecular core-valence effects with explicitly correlated wave functions: The atoms B–Ne and Al–Ar

Abstract: Correlation consistent basis sets have been optimized for accurately describing core-core and core-valence correlation effects with explicitly correlated F12 methods. The new sets, denoted cc-pCVnZ-F12 (n=D, T, Q) and aug-cc-pC(F12)VnZ (n=D, T, Q, 5), were developed by augmenting the cc-pVnZ-F12 and aug-cc-pVnZ families of basis sets with additional functions whose exponents were optimized based on the difference between all-electron and valence-electron correlation energies. The number of augmented functions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
256
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 282 publications
(259 citation statements)
references
References 40 publications
2
256
0
1
Order By: Relevance
“…[214] The resulting OptRI ABSs are compact and produce negligible RI errors compared to the basis set incompleteness error of the underlying OBS, both for correlation and relative energies. Although originally published to match the cc-pVnZ-F12 bases, the same methodology has been used to produce OptRI sets specifically matched to aug-cc-pVnZ bases, [215] to cc-pCVnZ-F12 bases, [51] for the light alkali and alkaline earth elements, [95] and for the group 11 and 12 transition metal elements. [186] It has been observed that while these OptRI basis sets are not optimal for producing the largest CABS singles energy corrections, if relative energies are considered the OptRI sets in conjunction with CABS singles corrections are sufficient to practically eliminate the HF basis set error.…”
Section: Auxiliary Basis Setsmentioning
confidence: 99%
See 2 more Smart Citations
“…[214] The resulting OptRI ABSs are compact and produce negligible RI errors compared to the basis set incompleteness error of the underlying OBS, both for correlation and relative energies. Although originally published to match the cc-pVnZ-F12 bases, the same methodology has been used to produce OptRI sets specifically matched to aug-cc-pVnZ bases, [215] to cc-pCVnZ-F12 bases, [51] for the light alkali and alkaline earth elements, [95] and for the group 11 and 12 transition metal elements. [186] It has been observed that while these OptRI basis sets are not optimal for producing the largest CABS singles energy corrections, if relative energies are considered the OptRI sets in conjunction with CABS singles corrections are sufficient to practically eliminate the HF basis set error.…”
Section: Auxiliary Basis Setsmentioning
confidence: 99%
“…[96,97] Correlation consistent basis sets for accurately describing core-core and core-valence correlation in an F12 framework have also been published for the elements LiAAr. [51,95] Two alternatives were proposed and denoted cc-pCVnZ-F12 and aug-cc-pC F12 VnZ, based on adding tight functions to the ccpVnZ-F12 and aug-cc-pVnZ basis sets, respectively. The number of additional functions added to construct the cc-pCVnZ-F12 sets is very small, especially at the QZ level, where only [1s1p1d] are added (for the first row elements), compared to [3s3p2d1f ] in aug-cc-pCVnZ.…”
Section: Correlation Consistent Basis Setsmentioning
confidence: 99%
See 1 more Smart Citation
“…In these MRCI-F12 calculations, which correlated also the As 3d 10 electrons, the geminal Slater exponent {β, in the nonlinear correlation factor, F (r 12 ) = -(1/β)exp(-βr 12 )} was set to 1.5 instead of the default value of 1.0 used for valence only calculations, as recommended for core-valence F12 calculations. 35 With the default frozen core, the total numbers of contracted and uncontracted configurations used in the MRCI-F12 calculations are 1516432 and 138334504, respectively. With the As 3d 10 electrons also active in the MRCI-F12…”
Section: Geometry Optimization Calculationsmentioning
confidence: 99%
“…20 The dynamic polarizabilities of S( 1 D) were obtained from the linear response MC-SCF theory 17 as implemented in DALTON quantum chemistry program. 18 The active space in this MCSCF calculation is defined as 6 electrons distributed in 13 MOs, which include 3s3p3d4s4p of S. The d-aug-cc-pCV6Z basis set 19 was employed in the MCSCF calculation. For Xe, we adopted the accurate values obtained from the relativistic many-body calculations in Ref.…”
Section: B Molecular Potential: Ab Initio Calculationsmentioning
confidence: 99%